Proposed Decision on Article IV Consultation Cycles. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The proposed Decision seeks to implement the staff's proposals related to Article IV consultation cycles in Review of the Fund's Mandate-Follow-Up on Modernizing Surveillance, which were endorsed in principle by the Executive Board on September 1, 2010. The goal is to provide for greater flexibility in consultation cycles and simplify the rules governing consultation cycles for members under a Fund arrangement or Policy Support Instrument (PSI).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Arrangement; Article; Consultation Cycle; PCL Arrangement; PP